What determines the financial performance of microfinance institutions in Bangladesh? a panel data analysis - Nasrin, Shamima; Rasiah, Rajah; Baskaran, Angathevar; Masud, Muhammad Mehedi (Springer Verlag, 2018)
While there is considerable expansion of microfinance institutions (MFIs) in the developing countries, there is a paucity of literature that examines the determinants of their Financial Performance (FP) among the Least Developed Countries (LDCs). This article seeks to investigate the determinants of FP of MFIs in Bangladesh over the period 2007–2013. Using two different measures of financial performance (portfolio yield and profit margin), the results indicate that the depth and breadth of social outreach can improve FP of MFIs. In particular, targeting women borrowers, increasing the average loan per borrower and increasing the number of active borrowers can contribute significantly to enhance the FP of MFIs. The results also show that, increasing savings and reducing operating expense can also contribute to increase MFIs’s financial performance.